Implementasi Nilai-Nilai Moderasi dan Toleransi Antar Umat Beragama dalam Menciptakan Kerukunan Masyarakat di Kota Pontianak Kalimantan Barat - Awaliya Safithri; Kawakib; Hasbi Ash Shiddiqi (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
The purpose of this study was to determine the religious life of the people of the city of Pontianak and to know the attitude of tolerance between religious communities in the Muslim minority environment in the people of the city of Pontianak and the views of Islamic morality on religious tolerance. Some of the objects in this study are: The living conditions of religious people in Pontianak City, West Kalimantan, Moderate forms of tolerance between religious communities in Pontinak City, West Kalimantan, Attitudes of moderation and tolerance values ​​between religious communities in creating harmony in Pontianak City, West Kalimantan. This study aims to measure the level of understanding of the values ​​of moderation and tolerance between religious communities in creating harmony in Pontianak City, West Kalimantan. The method chosen in this research is quantitative research methods, which can be interpreted as research methods based on the philosophy of positivism, used to examine certain populations or samples, sampling techniques are generally carried out randomly, data collection using research instruments, data analysis is quantitative. The operational definition of the variable in this study is the level of understanding of the population and leaders regarding the attitudes of values ​​of moderation and tolerance between religious communities in creating harmony in Pontianak City. The level of understanding that is measured: First, the attitude of values ​​of moderation and religious tolerance in the field of Aqidah including: not insulting or damaging other religious symbols, such as: holy books, places of worship, and symbols that are religious accessories; Second, the values ​​of moderation and religious tolerance in the field of worship, including: allowing other people to worship in peace; Third, the attitude of values ​​of moderation and religious tolerance in the field of Mu'amalah, including: Be fair in all worldly transactions, such as buying and selling, not discriminating in service when becoming a seller or not buying monopoly to fellow Muslims only when becoming a buyer with the intent to shutting down the efforts of non-Muslims and fourthly, religious moderation in the field of morals, including: being polite, such as if passing non-Muslims, excuse me, if there are non-Muslims who need help on the road, we will help, speak well when talking to non-Muslims